BUDGETARY CONTROL AND STANDARD COSTS IN INDUSTRIAL ACCOUNTING. - Dohr, James L. (The Accounting Review, 1932)
Abstract The subject of industrial accounting may be treated from any one of three points of view. First, it may be regarded primarily as a method of making and presenting an organized record of business happenings. Secondly, it may be regarded primarily as a method of exercising control over business events; during the period from 1918 to 1925 emphasis was concentrated largely on the "budgetary" aspects of industrial accounting. Finally, it may be regarded primarily as a means of measuring the efficiency of business operations. The subject of this paper is the coordination of the "budgetary" and "standard cost" aspects of industrial accounting. The budgetary idea in industrial accounting was probably borrowed from the municipal field. Municipal expenditures are controlled under the basic rule that no moneys are to be spent except as a statutory authorization or appropriation is made in advance. These appropriations are made after a study of possible revenues; a summary of the estimates and appropriations is designated as the budget. Adopted at the beginning of the fiscal period, the budget is used to control expenditures throughout that period. At the conclusion of the period a report is made showing a comparison of the expected results with actual income and expenditures. As applied to the industrial enterprise the central objective of budgetary procedure is the exercise of control over manufacturing operations.